Ethico-political Governmentality of Immigration and Asylum The Case of Ethiopia - Karal, Dilek (Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
Based on content analyses of three international organizations' policy reports and interviews with Somali refugees and refugee organizations, Dilek Karal examines the construction of ethico-political paradigm for immigration and asylum policies in Ethiopia. Departing from an assertion that ethico-political power is an intrinsic part of neo-liberal governmentality (and thus immigration and asylum policy formation), this volume unearths its mechanisms in Ethiopia's current immigration and refugee legislation and in global policy propositions moving forward. Ultimately, the exclusionary character of the propositions for Ethiopian states' governance of migrants is revealed through close interviews, data analysis, and applied analytics of governmentality method.